PENGEMBANGAN SISTEM PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Rohmah Istikomah (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
Islamic education is a very important lesson for elementary school’s age where this lesson is a basic knowledge for student’s in the future but, there is problem to apply Islamic lesson in this society because people still using traditional approach, where the point of value depends on cognitive aspect, whom teacher helping the student yo pass the final examination without any further values. And they built this tyoe of learning without develop attitude character, psychology development, society life, physical and mental state of students. So in this research, the researcher look for development Islamic education, the process and the execution of curriculum 2013 at elementary school. This research is using qualitative method with literarture review. The points of this research are Islamic education at elementary level using thematic approach for basic implementating involving juridical religious base and psychological and curriculum 2013 pointing on competency and character of students.